Towards a Taxonomy of Hybrid Warfare: Lessons from Crimea and the Donbas - Tarık SOLMAZ (Bulletin of "Carol I" National Defense University, 2025)
While “hybrid warfare” has attracted considerable interest among defense intellectuals for more than a decade, it still appears conceptually flawed. The main reason for this is that hybrid warfare remains a catch-all concept encompassing various types of actions. As such, the notion of hybrid warfare seems overly broad for academic analysis and national security planning. A classification of hybrid warfare is essential to distinguish its principal types. The research question for this article is, therefore: How can hybrid warfare be classified based on its modus operandi? In addressing this question, the article proposes a taxonomy based on David Kilcullen’s ideal types of counterinsurgency, namely, population-centric and enemy-centric models, given that hybrid warfare can manifest in two main forms, either as a direct challenge to military forces or as a malign influence on civilian populations and decision-makers. To illustrate this distinction, it examines two classic cases of the hybrid mode of warfare: Russia’s annexation of Crimea and covert occupation of the Donbas region. The findings suggest that Russia’s annexation of Crimea reflects a population-centric hybrid warfare approach, because it was essentially based mostly on non-violent actions rather than violent conflict. On the contrary, Russia’s covert occupation of the Donbas region indicates a more violent, enemy-centric model as it prioritizes military dominance.